Research on the Impact of Blockchain-Based Credible Return Information Mechanism on the Anti-Fraud Effect of Government Subsidies - Geng, Sihang (International Journal of Global Economics and Management, 2026)
Governments issuing consumer subsidies often falls prey to clever frauds that mostly work due to information imbalance left after you buy and get your hands on a thing. Bad guys do “phantom returns”, when they buy something subsidized and then claim the government’s money as a return, but don’t really send it back using fake shipping, so stores get their subsidy for nothing and can still sell the real stuff. This paper examines in detail the effect that if we were to adopt an actual working credible return information system, on such systemic scam of Government subsidy. Using the characteristics that cannot be changed, were scattered around, and could transparently see things by means of distributed ledger technology, we integrated e-commerce platforms, 3PLs, government auditors all under one roof into a cryptographic consortium network. In this article I make comparison from the recent pilots which has been researched and proved by using the data of the introduction on intelligent contract –automatic verification will greatly increase detection, prevention, and punishment of fraud. When there were less of the financial leaks there would be a lesser amount of time to do an audit, instead of after something has been found it is now during: In the end, it gives out very important theoretical framework and useful policy suggestions for government agencies wanting to make public financial stimulation projects both more economic efficient and administratively sound by using modern crypto technology in strategic ways.